Blackout ebook A novel. - Elsberg, Marc (2017)
"Fast, tense, thrilling — and timely: this will happen one day. Highly recommended." —Lee Child, #1 New York Times bestselling author of the Jack Reacher series This is no accident. This is no act of God. This is a Blackout. When the lights go out one night, no one panics. Not yet. The lights always come back on soon, don't they? Surely it's a glitch, a storm, a malfunction. But something seems strange about this night. Across Europe, controllers watch in disbelief as electrical grids collapse. There is no power, anywhere. A former hacker and activist, Piero investigates a possible cause of the disaster. The authorities don't believe him, and he soon becomes a prime suspect himself. With the United States now also at risk, Piero goes on the run with Lauren Shannon, a young American CNN reporter based in Paris, desperate to uncover who is behind the attacks. After all, the power doesn't just keep the lights on—it keeps us alive.